Aero-ZnS prepared by physical vapor transport on three-dimensional networks of sacrificial ZnO microtetrapods - Ursaki, Veaceslav; Braniste, Tudor; Zalamai, Victor; Rusu, Emil; Ciobanu, Vladimir; Morari, Vadim; Podgornii, Daniel; Ricci, Pier Carlo; Adelung, Rainer; Tiginyanu, Ion (Beilstein Journal of Nanotechnology, 2024)
Aeromaterials represent a class of increasingly attractive materials for various applications. Among them, aero-ZnS has been produced by hydride vapor phase epitaxy on sacrificial ZnO templates consisting of networks of microtetrapods and has been proposed for microfluidic applications. In this paper, a cost-effective technological approach is proposed for the fabrication of aero-ZnS by using physical vapor transport with Sn2S3 crystals and networks of ZnO microtetrapods as precursors. The morphology of the produced material is investigated by scanning electron microscopy (SEM), while its crystalline and optical qualities are assessed by X-ray diffraction (XRD) analysis and photoluminescence (PL) spectroscopy, respectively. We demonstrate possibilities for controlling the composition and the crystallographic phase content of the prepared aerogels by the duration of the technological procedure. A scheme of deep energy levels and electronic transitions in the ZnS skeleton of the aeromaterial was deduced from the PL analysis, suggesting that the produced aerogel is a potential candidate for photocatalytic and sensor applications.
Keywords: aeromaterial; crystallographic structure; luminescence; physical vapor transport; scanning electron microscopy (SEM); X-ray diffraction (XRD)